Pengaruh Destination Image dan Aktivitas Media Sosial terhadap Minat Berkunjung melalui Destination Personality pada Taman Wisata Alam Gunung Papandayan - Rinda Sekar Arum; Dini Turipanam Alamanda; Husni Muharam (POLITEKNIK LP3I, 2026)
This study investigates the influence of destination image and social media activities on tourists’ intention to visit through the mediating role of destination personality at Gunung Papandayan Nature Tourism Park. A quantitative explanatory approach was applied in this research. The study involved 200 respondents selected through purposive sampling, consisting of individuals who were familiar with or had received information about Gunung Papandayan from social media platforms. Data were collected using Likert-scale questionnaires and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) supported by SmartPLS software. The findings indicate that both destination image and social media activities have a positive and significant effect on destination personality. Furthermore, destination personality significantly enhances tourists’ intention to visit. In contrast, destination image and social media activities do not directly affect visit intention in a significant way. Mediation analysis reveals that destination personality acts as an intervening variable linking destination image and social media activities with tourists’ visit intention. These results suggest that establishing a strong destination personality can effectively strengthen tourists’ interest in visiting Gunung Papandayan Nature Tourism Park.